PENERAPAN MODEL PEMBELAJARAN DIRECT INSTRUCTION UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATERI LAGU DAERAH DI KELAS IV SDN 1 TELAGA BIRU - Akbar Tuna; Abd. Hamid Isa; Fandi H. Binggo (Jurnal Ilmu Pendidikan UMGo, 2025)
Learning motivation plays an important role in determining students’ engagement and success in the learning process. In elementary education, particularly in Cultural Arts and Crafts (SBdP) subjects, students are expected not only to understand theoretical knowledge but also to actively participate in artistic learning activities such as singing regional songs. However, in many classroom situations, students show low motivation to participate in these activities. This study aims to improve students’ learning motivation through the implementation of the Direct Instruction learning model in regional song learning. This research employed Classroom Action Research (CAR) based on the Kemmis and McTaggart model consisting of four stages: planning, action, observation, and reflection. The research was conducted in two cycles. The participants were 26 fourth-grade students of SDN 1 Telaga Biru, Gorontalo Regency. Data were collected through observation, interviews, tests, and documentation, and analyzed using descriptive percentage analysis. The results showed that the implementation of the Direct Instruction model significantly improved students’ learning motivation. In the initial observation, only 15.4% of students showed high learning motivation. After the implementation of Cycle I, the percentage increased to 65%. In Cycle II, students with high learning motivation reached 96%, exceeding the predetermined success indicator of 86%. These findings indicate that the Direct Instruction model provides structured learning stages that encourage students to actively participate in the learning process. Therefore, the Direct Instruction model can be considered an effective instructional strategy for improving students’ learning motivation in elementary school learning.